2019
DOI: 10.7150/ijbs.28392
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Human Induced Pluripotent Stem Cells-Endothelia Cells Promotes Postnatal Angiogenesis in Mice Bearing Ischemic Limbs

Abstract: Induced pluripotent stem cell (iPSC) derived endothelial cells (ECs) is a novel therapeutic option for ischemic diseases. Although the detailed mechanism of this novel therapy remains unknown, emerging evidence has demonstrated that exosomes derived from hiPSC-ECs play a critical role in this approach. In this study, we first isolated and characterized the exosomes from iPSCs-ECs (hiPSC-EC-Exo) and determined the functional roles of hiPSC-EC-Exo in neovascularization and the underlying mechanism. Further, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 39 publications
(45 reference statements)
1
37
0
1
Order By: Relevance
“…Similarly, exosomes derived by iMSCs promoted the proliferation of human fibroblasts in vitro in a dose-dependent manner while iMSCs-derived exosomes enhanced the viability and cell cycle progression in human keratinocytes and human dermal fibroblasts (Kim et al, 2018). Ye et al (2019) in one of their studies treated bovine aortic endothelial cells with 100 µg/ml of hiPSC-CM-derived exosomes and found a significant increase in cell proliferation when compared to control (no exosomes). Khan et al (2015) reported that mouse hearts treated with ESC-derived exosomes promote myocyte proliferation by enhancing cardiomyocyte cycling, as evidenced by both BrdU+ (S-phase) and phosphorylated histone H3 (PH3+; M-phase) cardiomyocytes, at 28 days of infarction when compared to those treated with embryonic fibroblastsderived exosomes orsaline.…”
Section: Pro-cell Cycle Effects Of Ipsc Exosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, exosomes derived by iMSCs promoted the proliferation of human fibroblasts in vitro in a dose-dependent manner while iMSCs-derived exosomes enhanced the viability and cell cycle progression in human keratinocytes and human dermal fibroblasts (Kim et al, 2018). Ye et al (2019) in one of their studies treated bovine aortic endothelial cells with 100 µg/ml of hiPSC-CM-derived exosomes and found a significant increase in cell proliferation when compared to control (no exosomes). Khan et al (2015) reported that mouse hearts treated with ESC-derived exosomes promote myocyte proliferation by enhancing cardiomyocyte cycling, as evidenced by both BrdU+ (S-phase) and phosphorylated histone H3 (PH3+; M-phase) cardiomyocytes, at 28 days of infarction when compared to those treated with embryonic fibroblastsderived exosomes orsaline.…”
Section: Pro-cell Cycle Effects Of Ipsc Exosomesmentioning
confidence: 99%
“…While the primary goal of stem cell-based therapy is to generate new cardiac muscle, recent data from both clinical and preclinical studies have indicated that transplanted stem cells may exert their functional beneficial effects largely through their secretome, by which the paracrine activity of the transplanted cells is mediated in part through their secreted vesicles (Merino-Gonzalez et al, 2016). Significant preclinical developments of exosome-based regeneration medicine have been achieved thus far through recognizing that it is the paracrine cues from transplanted iPSCs and/or its derivatives, that impart the major beneficial effects of regeneration within the injured tissues, rather than the direct effect of surviving transplanted cells Dougherty et al, 2017Dougherty et al, , 2018Ye et al, 2019). Furthermore, recent studies establish that exosomes derived by donor cells play a critical role in this paracrine regenerative mechanism Merino-Gonzalez et al, 2016;Ju et al, 2018;Youn et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, exosomes isolated from hiPSC-ECs contained miR-199b-5p and promoted angiogenesis. [52] Exosomes isolated from cardiosphere-derived cells with expression of Lamp2b had cardiomyocyte specific peptide on their surface and increased their uptake by cardiomyocytes. [53] Therefore, the EVs can be engineered by using different cells, cocultured cells, and biological approaches.…”
Section: Hipsc Derived Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Animals were euthanized 14 days post-treatment and the authors demonstrated that treatment with iPSC-ECs delivered within SHIELD-2.5 resulted in significantly greater arteriole density and improved formation of large microvessels, features that usually play a prominent role in neovascularization [102]. In 2019, Ye et al focused their attention on the exosomes derived from human iPSC-ECs (hiPSC-EC-Exo) [103]. Exosomes are vesicles containing miRNAs and are able to protect them from RNAases but they also release miRNAs which are highly involved in the regulation of angiogenesis.…”
Section: Ability Of Ipsc-ecs To Induce In Vivo Neovascularizationmentioning
confidence: 99%